COVID-19 and Orthopaedic International Humanitarianism. (February 2021) - Talsania, Alec J.; Lavy, Chris; Khanuja, Harpal S.; Chambers, Hank; Kelly, Nancy A.; Gardner, Richard O. E.; Nelson, Scott; Wambisho, Biruk L.; Alexis, Francel; Lalonde, Donald H.; Coughlin, R. Richard; Vosseller, J. Turner; et al.
Abstract : As the world continues to adjust to life with COVID-19, one topic that requires further thought and discussion is whether elective international medical volunteerism can continue, and, if so, what challenges will need to be addressed. During a pandemic, the medical community is attentive to controlling the disease outbreak, and most of the literature regarding physician involvement during a pandemic focuses primarily on physicians traveling to areas of need to help treat the disease. As a result, little has been written about medical volunteerism that focuses on medical treatment unrelated to the disease outbreak. In a world-wide pandemic, many factors are to be considered in determining whether, and when, a physician should travel to another region to provide care and training for medical issues not directly related to the pandemic. Leaders of humanitarian committees of orthopaedic surgery subspecialties engaged with one another and host orthopaedic surgeons and a sponsoring organization to provide thoughtful insight and expert opinion on the challenges faced and possible pathways to provide continued orthopaedic support around the globe. Although this discussion focuses on international orthopaedic care, these suggestions may have a much broader application to the international medical community as a whole.